The challenges confronting the training needs assessment in Saudi Arabian higher education - John Mulyata (International Journal of Engineering Business Management, 2022)
This research examines the problems encountered by the Training Needs Assessment (TNA) system from the perspective of faculty members and Human Resources (HR) managers in emerging public universities in the Saudi Arabian Higher Education sector. It aims to understand how problems with this will affect the success rate of Training and Development (T&D) curriculums. The research comprises an analytical study using a case study method of analysis. Qualitative data collection was carried out using semi-structured interviews with 75 senior managers and faculty members of four selected universities, selected using purposive non-random sampling. The data was analysed using Thematic Analysis (TA). The results highlight the insufficiency of the TNA techniques applied to ascertain training requirements. The primary obstacles to successful TNA were inadequate HR processes, insufficiently experienced HR directors, poor engagement, and favouritism concerning the selection of candidates for T&D. These issues affect the enthusiasm of those in the department. Additionally, resources required for T&D, particularly time and money, are misused, which could influence the growth potential of the universities against the country’s Vision 2030 plan. The findings indicate procedural differences in selecting and approving staff requests for Human Resource Development (HRD) support, managerial discretion in selecting participants for HRD programmes, and selective or restricted access to HRD programmes for foreign-born employees, which raises significant questions about equality policies. This study is unique as a contribution to the literature in exploring the challenges faced by the TNA process in Saudi Arabian Higher Education, therefore broadening understanding in the field as a whole, especially concerning the developing countries and Gulf Cooperation Council of Nations. The study concludes that there is currently unsatisfactory commitment in determining the staff training needs by the HR departments of Saudi Arabian public universities, which damages morale and leads to a lack of faith between HR directors and departmental staff. Finally, this study contributes to the area of policy decision-making by reporting the present situation surrounding the issues related to the application of TNA in T&D.